Trust and shared decision‐making among individuals with multiple myeloma: A qualitative study. (5th October 2021) - Whitney, Robin L.; White, Anne Elizabeth Clark; Rosenberg, Aaron S.; Kravitz, Richard L.; Kim, Katherine K.
Abstract: Background: Multiple myeloma (MM) is an incurable cancer with complex treatment options. Trusting patient–clinician relationships are essential to promote effective shared decision‐making that aligns best clinical practices with patient values and preferences. This study sought to shed light on the development of trust between MM patients and clinicians. Methods: Nineteen individual semi‐structured interviews were conducted with MM patients within 2 years of initial diagnosis or relapse for this qualitative study. Interviews were recorded and transcripts were coded thematically. Results: We identified three main themes: (1) externally validated trust describes patients' predisposition to trust or distrust clinicians based on factors outside of patient–clinician interactions; (2) internally validated trust describes how patients develop trust based on interactions with specific clinicians. Internally validated trust is driven primarily by clinician communication practices that demonstrate competence, responsiveness, listening, honesty, and empathy; and (3) trust in relation to shared decision ‐ making describes how patients relate the feeling of trust, or lack thereof, to the process of shared decision‐making. Conclusion: Many factors contribute to the development of trust between MM patients and clinicians. While some are outside of clinicians' control, others derive from clinician behaviors and interpersonal communication skills. These findings suggest the possibility that trust can be enhanced through communication training or shared decision‐making tools that emphasize relational communication. Given the important role trust plays in shared decision‐making, clinicians working with MM patients should prioritize establishing positive, trusting relationships. Abstract : Patient–clinician trust is influenced by both external factors and clinician behaviors in the context of multiple myeloma. Trust between patients with myeloma and their clinicians is an important aspect of shared decision‐making.